PERUMUSAN NILAI TAMBAH SUATU KAWASAN PARIWISATA: SUATU KERANGKA PEMIKIRAN DARI PENDEKATAN PEMASARAN - Ivantia Savitri Mokoginta (Bina Ekonomi, 2000)
This paper proposes the interaction of market, internal and competitor factors in positioning determination of tourism destination. What area of concerned of each factor how these factors interrelated in positioning determination is further explained.